PEMANFAATAN LAHAN KOSONG UNTUK BUDIDAYA KANGKUNG SEBAGAI UPAYA PENINGKATAN KETAHANAN PANGAN DI DESA NITUWU BOHO - Selamat Duho; Rantonius Warae; Batasi Waruwu; Kris Sapta Riang Daeli; Hasrat Taniat Buulolo; Markus Halawa; Miranti Wulan Zega; Junhar Laia; Yurnian Buulolo; Teni Laia (Universitas Nias Raya, 2025)
The 2025 community service program was implemented in Nituwu Boho Village, Lolowau District, South Nias Regency, as a form of the Tri Dharma of Higher Education implementation. This activity lasted approximately 40 days, from July 11 to August 20, 2025, and aimed to provide students with practical experience, learning, and skills while supporting the village development program. Based on initial observations, Nituwu Boho Village was running a food security program, but there were still unused vacant lands that had not been utilized optimally. Therefore, the community service program focused on the utilization of vacant land for the cultivation of water spinach (kangkung) as an effort to enhance the village’s food security. The implementation method was participatory, emphasizing communication and interaction between students, village officials, and the local community. The community played an active role as innovators and activators in every stage of the activity, from land preparation, planting, and maintenance, to harvesting the water spinach. This activity aimed not only to increase household food availability but also to raise community awareness about the importance of productive land use. The results showed that water spinach cultivation can be carried out easily, with relatively low costs, and provides quick yields. The program received full support from the residents of Nituwu Boho Village and ran smoothly. Therefore, this community service activity is expected to contribute to strengthening village food security and serve as a sustainable example of utilizing vacant land effectively.